Zooplâncton do Pantanal de Mato Grosso : o papel dos bancos de macrófitas sobre a estruturação da comunidade - Brito, Maiara Tábatha da Silva (2021)
For many years, community ecology studies have aimed to investigate the biodiversity of species in the most varied ecosystems, filling in distribution gaps. Despite this effort, some aquatic groups and ecosystems can still be considered under-investigated, as is the case of the zooplanktonic groups in limnetic ecosystems in the central region of Brazil. Records of the occurrence and distribution of these species are essential for carrying out ecological studies that will help in understanding the processes and factors responsible for generating diversity patterns. In this context, different approaches have attracted attention, such as the use of indices that determine the local and species contribution to the total beta diversity (LCBD and SCBD, respectively), and those based on information about species’ functional traits. In light of this, the present thesis had the objective of investigating the zooplanktonic community of the Pantanal do Mato Grosso, central Brazil, considering not only the pelagic zone but also the littoral zone of lakes (marked by the presence of macrophyte beds). The first chapter was designed to investigate the species richness, LCBD and SCBD of 50 lakes in the Pantanal (pelagic and littoral zones). It was concluded that conservation studies for floodplain should consider the different groups (rotifers and cladocerans) and the different zones of the lakes, given that the responses vary between groups and that the littoral zones add information about the biodiversity of the groups and are capable of revealing different patterns. The second chapter aimed to investigate the species richness and composition of cladocerans in the littoral zones of 50 lakes in the Pantanal do Mato Grosso and, at the same time, to carry out a compilation of studies on the group for the hydrographic regions (HRs) of the state of Mato Grosso (MT). Seventeen new occurrences of cladocerans were recorded for MT state, and it was noted that the Paraguay River HR is the most studied. It was concluded that only 72.6 % of the cladocerans of MT are known, and the HRs of the Amazonas and Tocantins-Araguaia Rivers are the least studied. The third chapter aimed to evaluate the taxonomic diversity, functional composition and functional diversity of rotifers and, in addition, to understand which factors drives diversity in this group in the lakes of the Pantanal do Mato Grosso. It was observed that the diversity of rotifers was influenced both by biotic pressure (cladocerans and cyanobacteria) and by large scale spatial patterns. The results observed in the three chapters of this thesis contribute to knowledge on the zooplanktonic biodiversity of the Pantanal do Mato Grosso, and they highlight the importance of considering the littoral zones, marked by the presence of macrophytes, and of using different approaches in biodiversity studies.